HUBUNGAN POSTUR KERJA JANGGAL SAAT MENJARING IKAN TERHADAP KELUHAN LOW BACK PAIN PADA PERKUMPULAN NELAYAN: THE RELATIONSHIP OF AN INCREDIBLE WORK POSTURE WHEN FISHING FISH TO COMPLAINTS OF LOW BACK PAIN IN FISHERMEN'S ASSOCIATIONS - Diina Maulina; Fitri Sari Dewi; Sri Puji Lestari (YCMM, 2020)
Awkward Work Posture is a body position that deviates significantly from the normal position when doing work. Low back pain is pain that is felt in the area around the lower back, it can be local pain or radicular pain. Many fishermen's work positions are not ergonomic, such as bending over, body position when pulling nets and sitting for too long. This study aims to determine the relationship between awkward working postures when catching fish and complaints of low back pain in the mermaid fishing association working area of ​​Tanjungpinang Health Center in 2020. The research method used is a quantitative method with an analytical survey research design with a cross sectional research design on each subject involved. using the Chi-square test, which compares the frequency of occurrence (observations) with the frequency of expectations (expectations) with a sample of 44 respondents. Suggestions for fishermen are to carry out routine checks at the Puskesmas by health workers every month so that they can control their health by limiting the duration of work of fishermen so that they do not interfere with their work activities. For the Puskesmas to provide promotions or counseling to fishermen so that complaints of low back pain can be reduced.